2022
DOI: 10.3892/ol.2022.13224
|View full text |Cite
|
Sign up to set email alerts
|

Ophiopogonin B induces gastric cancer cell death by blocking the GPX4/xCT‑dependent ferroptosis pathway

Abstract: Ophiopogonin B (OP-B) is extensively applied as a treatment for pulmonary disease and is reported to suppress lung cancer. However, further study is needed to determine whether OP-B suppresses gastric cancer (GC). The mRNA levels of prostaglandin-endoperoxide synthase 2 (Ptgs2) and ChaC glutathione-specific gamma-glutamylcyclotransferase 1 (Chac1) were determined using quantitative PCR. Ptgs2 and Chac1 mRNA levels were significantly increased in GC cancer tissues compared with those of adjacent normal controls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…[ 101 ] Ophiopogon B was capable of provoking ferroptosis in GC cells by preventing the GPX4/xCT system. [ 102 ] Self‐assembled nanoparticles accelerated the process of lipid peroxidation by increasing the depletion of GSH and stimulating SO2 production. Additionally, they hampered the malignant development of GC by suppressing GPX4 expression and allowing ferroptosis to occur.…”
Section: Ferroptosis In Gi Cancersmentioning
confidence: 99%
“…[ 101 ] Ophiopogon B was capable of provoking ferroptosis in GC cells by preventing the GPX4/xCT system. [ 102 ] Self‐assembled nanoparticles accelerated the process of lipid peroxidation by increasing the depletion of GSH and stimulating SO2 production. Additionally, they hampered the malignant development of GC by suppressing GPX4 expression and allowing ferroptosis to occur.…”
Section: Ferroptosis In Gi Cancersmentioning
confidence: 99%
“…A number of studies have proved that some natural compounds ( Table 1 ) such as dihydroartemisinin ( Yuan et al, 2020 ), artesunate ( Zhang Q. et al, 2021 ),sulforaphane ( Iida et al, 2021 ), curcumin ( Tang X. et al, 2021 ), bufotalin ( Zhang W. et al, 2022 ), sanguinarine ( Xu R. et al, 2022 ), sinapine ( Shao et al, 2022 ), solasonine ( Zeng et al, 2022 ), ophiopogonin B ( Zhang L. et al, 2022 ), red ginseng polysaccharide ( Zhai et al, 2022 ) Dihydroisotanshinone I ( Wu et al, 2021 ).inhibits the proliferation, colony formation and induces ferroptosis of lung cancer cells by the interfering mRNA and/or protein expression and/or degradation of SLC7A11 or GPX4. Apart from natural compounds, some drugs that have been marketed ( Table 1 ) such as Vorinostat ( Zhang T. et al, 2021 ), Orlistat ( Zhou W. et al, 2021 ) have also been found to act as ferroptosis inducers in lung cancer cells via inhibiting System X c − /GSH/GPX4 axis.…”
Section: Potential Roles Of Targeting System X C ...mentioning
confidence: 99%
“…Ophiopogonin B is an active compound extracted from Radix Ophiopogon japonicus with anticancer activity. Recently, Ophiopogonin B was demonstrated to decrease GPX4/xCT expression in AGS and NCI‐N87 cells, leading to ferroptosis (Zhang, Li, et al, 2022b). Moreover, a recent study has shown that nanoparticles loaded with sulfur dioxide polymer predrugs were able to promote ferroptosis in GC cells by accelerating lipid oxidation and reducing GPX4 (Xia et al, 2022).…”
Section: Compounds Prevent Gc Via Regulated Cell Deathmentioning
confidence: 99%